SKEMA ANUITAS SYARIAH UNTUK DANA PENSIUN STUDI KASUS DANA PENSIUN LEMBAGA KEUANGAN SYARIAH - Waluyo, Waluyo; Rayhan Difa, Muhammad Ahnaf; Agustin, Anisa Puji; Nurlisa, Yani Hesti (JISEF : Journal Of International Sharia Economics And Financial, 2025)
This study examines the concept of Sharia annuities in the management of pension funds through Sharia Financial Institution Pension Funds (DPLK Syariah) in Indonesia. DPLK Syariah has emerged as an alternative option for pension fund management that complies with Sharia principles, namely avoiding elements of riba (usury), gharar (uncertainty), and maisir (gambling). The implementat ion of the Sharia annuity scheme is carried out in two main phases: the accumulation phase and the benefit payment phase, all of which utilize Sharia contracts such as wakalah bil ujrah and ijarah. This study employs a literature review method to explain the basic concept, scheme implementation, and the challenges faced in applying Sharia annuities in DPLK Syariah. The findings of this study indicate that although there is great potential for the development of Sharia annuities, challenges such as low public awareness of Sharia finance and the limited availability of halal investment instruments remain the main obstacles. Collaboration between the government, financial authorities, and industry players is needed to improve public understa nding and expand Sharia-compliant investment instruments so that the management of pension funds based on Sharia annuities can be carried out more effectively.